The Northern Territory's cask wine levy: Health and taxation policy implications - Gray, Dennis; Chikritzhs, Tanya; Stockwell, Tim (1999)
A study examines the effect of the application, and removal, in the Northern Territory of a levy on the sale of cask wine - a beverage shown to contribute disproportionately to alcohol-related harm. Prior to the introduction of the levy, quarterly per capital consumption of cask wine among persons aged 15 and older was 0.73 liters. During the levy period, this fell to .49 liters and following removal of the levy rose to 0.58 liters. Imposition of the levy had no significant effect on the consumption of other beverages. The study concludes that taxation is an effective means of reducing excessive alcohol consumption and related harm. In the interest of public health, support should be given to the introduction of a tiered tax based on alcohol content.